2014
DOI: 10.1038/eye.2014.43
|View full text |Cite
|
Sign up to set email alerts
|

High intraocular pressure is associated with cardiometabolic risk factors in South Korean men: Korean National Health and Nutrition Examination Survey, 2008–2010

Abstract: Objective Elevated intraocular pressure (IOP) contributes to the progression of visual defects such as glaucoma. This study determined whether metabolic syndrome (MetS) and cardiovascular risk factors are associated with IOP in South Korean men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 43 publications
(74 reference statements)
5
42
2
Order By: Relevance
“…9,21,22 Obesity is also a risk factor of hypertension, and high blood pressure has been reported to increase pressure in the intraocular ciliary artery, and thereby, to stimulate the generation of aqueous humour, which increases IOP. It is has been well established that blood pressure is correlated with IOP, 22,23 and similarly, in the present study, BMI and blood pressure were both positively correlated with IOP.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…9,21,22 Obesity is also a risk factor of hypertension, and high blood pressure has been reported to increase pressure in the intraocular ciliary artery, and thereby, to stimulate the generation of aqueous humour, which increases IOP. It is has been well established that blood pressure is correlated with IOP, 22,23 and similarly, in the present study, BMI and blood pressure were both positively correlated with IOP.…”
Section: Discussionsupporting
confidence: 66%
“…17 Unlike many reports that indicated IOP to be positively correlated with serum TC and TG levels, no consistent results indicate the correlation of IOP with HDL-C and LDL-C. Although a report indicated a positive correlation between HDL-C and IOP, 23 another report conversely indicated a negative correlation. 15,25 In this study, univariate regression showed a negative correlation between HDL-C and IOP but a positive correlation between LDL-C and IOP, which are consistent with the findings of a recent study.…”
Section: Discussioncontrasting
confidence: 43%
“…Indeed, there is research showing increased levels of TC, TG and LDL, and decreased HDL in POAG and NTG patients [35][36][37]. Furthermore, one population analysis has linked dyslipidemia with increased IOP in people not receiving glaucoma treatment, suggesting that hyperlipidemia may play a role in the onset of glaucoma [38]. In this study, we have found higher levels of TC in glaucoma patients and TG in NTG patients only, compared to healthy controls.…”
Section: Discussionsupporting
confidence: 60%
“…High BP and diabetes are well known established risk factors associated with cardiovascular disease (CVD). Furthermore, several studies have demonstrated the positive association between IOP and cardiometabolic risk factors or metabolic syndrome 6 7. Therefore, the relationship between IOP and cardiovascular risk factors raises the possibility that increased IOP may be associated with CVD.…”
Section: Introductionmentioning
confidence: 99%